Semiconductor Heterostructure SrTiO3/CeO2 Electrolyte Membrane Fuel Cells. Issue 5 (1st January 2020) - Shi, Quan; Chen, Jiahe; Xing, Yueming; Zhu, Bin; Wu, Yan
Abstract : Semiconductor heterostructure SrTiO3 /CeO2 (STO/CeO2 ) membrane was used as the electrolyte material of low-temperature solid oxide fuel cells. This STO/CeO2 membrane demonstrated a high ionic conductivity of 0.24 S cm −1 under fuel cell conditions at 550°C, and also its fuel cell delivered a maximum power output of 745.6 mW cm −2 at the same temperature. Moreover, the high electronic conductivity of CeO2 is blocked by the STO/CeO2 semiconductor heterojunction, thus resulting in the open circuit voltage increasing from 0.90 to 1.09 V at 550°C. The semiconductor heterointerface is found to play an important role in inhibiting the electron transfer between CeO2 particles. Thus, this work makes it feasibility of using semiconductor materials as the electrolyte by constructing heterojunctions to suppress the electronic conductivity.